An automated instrument for intrauterine insemination sperm preparation - Alex Jafek (Nature Portfolio, 2020)
Abstract Sperm preparation is critical to achieving a successful intrauterine insemination and requires the processing of a semen sample to remove white blood cells, wash away seminal plasma, and reduce sample volume. We present an automated instrument capable of performing a sperm preparation starting with a diluted semen sample. We compare our device against a density gradient centrifugation by processing 0.5 mL portions of patient samples through each treatment. In 5 min of operating time, the instrument recovers an average of 86% of all sperm and 82% of progressively motile sperm from the original sample while removing white blood cells, replacing the seminal plasma, and reducing the volume of the sample to the clinically required level. In 25 min of operating time, density gradient centrifugation recovers an average of 33% of all sperm and 41% of progressively motile sperm. The automated instrument could improve access to IUI as a treatment option by allowing satellite doctor’s offices to offer intrauterine insemination as an option for patients without the clinical support required by existing methods.